Preventative behaviours and COVID-19 infection in a Canadian cohort of people living with HIV - Keely Hammond; Terry Lee; Branka Vulesevic; Joel Singer; Judy Needham; Ann N. Burchell; Hasina Samji; Sharon Walmsley; Mark Hull; Mohammad-Ali Jenabian; Jean-Pierre Routy; Shari Margolese; et al. (AIDS Research and Therapy, 2023)
Abstract Few studies have examined preventative behaviour practices with respect to COVID-19 among people living with HIV (human immunodeficiency virus). Using a cross-sectional survey from a Canadian Institutes of Health Research Canadian HIV Trials Network study (CTN 328) of people living with HIV on vaccine immunogenicity, we examined the relationships between participant characteristics and behavioural practices intended to prevent COVID-19 infection. Participants living in four Canadian urban centers were enrolled between April 2021–January 2022, at which time they responded to a questionnaire on preventative behaviour practices. Questionnaire and clinical data were combined to explore relationships between preventive behaviours and (1) known COVID-19 infection pre-enrolment, (2) multimorbidity, (3) developing symptomatic COVID-19 infection, and (4) developing symptomatic COVID-19 infection during the Omicron wave. Among 375 participants, 49 had COVID-19 infection pre-enrolment and 88 post-enrolment. The proportion of participants reporting always engaging in preventative behaviours included 87% masking, 79% physical distancing, 70% limiting social gatherings, 65% limiting contact with at-risk individuals, 33% self-isolating due to symptoms, and 26% self-quarantining after possible exposure. Participants with known COVID-19 infection pre-enrolment were more likely to self-quarantine after possible exposure although asymptomatic (65.0% vs 23.4%, p < 0.001; Chi-square test). Participants with multiple comorbidities more likely endorsed physical distancing (85.7% vs 75.5%, p = 0.044; Chi-square test), although this was not significant in logistic regression analysis adjusted for age, sex, race, number of household members, number of bedrooms/bathrooms in the household per person, influenza immunization, and working in close physical proximity to others. Overall, participants reported frequent practice of preventative behaviours.